2016
DOI: 10.5430/ijba.v7n5p9
|View full text |Cite
|
Sign up to set email alerts
|

Succession Planning in Black-Owned Family Businesses: A South African Perspective

Abstract: A significant number of businesses existing in South Africa originated as family-owned businesses and contribute substantially to employment creation, poverty eradication and wealth creation. However, globally the longevity of family businesses through generations remains a major cause for concern for all stakeholders. South African economy is characterised by a history of apartheid, where prior to 1994, the black majority only owned less than 5 percent of the businesses active in the economy. The economy is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 27 publications
(26 reference statements)
0
15
0
Order By: Relevance
“…Furthermore, such a process guarantees smooth running, sustainability and good performance of family businesses in the absence of the founder. This is because, as Gomba and Kele (2016) observe, successors selected by business founders have an increased level of commitment to the business, which contributes to better business performance.…”
Section: Resultsmentioning
confidence: 98%
“…Furthermore, such a process guarantees smooth running, sustainability and good performance of family businesses in the absence of the founder. This is because, as Gomba and Kele (2016) observe, successors selected by business founders have an increased level of commitment to the business, which contributes to better business performance.…”
Section: Resultsmentioning
confidence: 98%
“…In South Africa, copreneurs exist within the framework of two fields, namely SMMBs and family business. Family businesses in South Africa account for around 80 percent of businesses thus they play an extremely important role in terms of job creation and poverty alleviation in both the formal and informal sectors (Gomba & Kele, 2016). In fact, the Siamese twins of unemployment and poverty, are a scourge, which small businesses have continually been peddled as solution.…”
Section: Obstacles To Smmbs Successmentioning
confidence: 99%
“…There exist various studies about the transfer of management and its management, heir or successor selection, and most sought heir or successor characteristics in related literature such as Cesaroni & Sentuti (2017), Chua et al (1999), Devany (2006), Gomba & Kele (2016), Güller (2010), and Sharma & Rao (2000). An extensive literature review (e.g., Yu et al, 2012;Bau et al, 2013) indicated that the majority of the related studies had used questionnaire data, convenience sampling, small sample sizes, conceptual analyses and descriptions, and qualitative data analyses.…”
Section: Introductionmentioning
confidence: 99%